Harmonic mitigation project, Work Package 1b: Model development - Atheer Habash (2020)
The work reported here describes the creation and validation of a modelling environment that is ultimately intended to support the development and testing of harmonic mitigation algorithms to be overlaid on existing (modelled) PV inverters.The chosen modelling environment for this work is MATLAB/Simulink. This tool provides component libraries and analysis tools for fundamental frequency modelling and time-series simulation of electrical power systems and also facilitates harmonic time-series modelling and analysis. Additionally, MATLAB/Simulink is fully integrated with the real-time simulation software RT-LAB, thus allowing hardware-in-the-loop analysis in Work Package 4.Establishing a modelling environment has been undertaken in a number of steps that fall into two key stages of development. Stage One was the development of a network model within MATLAB/Simulink, based on a WPD provided model. Stage Two was demonstration that the MATLAB/Simulink model can appropriately perform electromagnetic transient (EMT) simulation and analysis of the modelled network. This EMT simulation covered a period of three weeks, and included fundamental and harmonic components. Validation was carried out within each development stage.Stage One validation was aimed at demonstrating that the developed network model effectively represented the topology and electrical characteristics (such as impedances) of the actual network. This was achieved through a series of six power flow studies plus a frequency sweep assessment. Results from the developed model were compared to a reference WPD-provided model. Good agreement has been found between the results of these tests from the two models, and where appropriate to SCADA; it is concluded that the MATLAB/Simulink model provides a satisfactory representation of the system under study.Stage Two validation was aimed at demonstrating EMT simulation and realism of simulation results over time. Initially this focused on fundamental frequency behaviour; where modelled active and reactive power flows across the system boundary were compared to SCADA and found to be realistic. Modelled voltages from the simulation (which excluded tap changer control) were also investigated and found to be satisfactory. Modelled harmonic behaviour was assessed by comparison to measurement data from temporarily installed power quality monitors. Assessment included current and voltage harmonics, considering overall levels and variation between phases for the 5th, 7th 11th an 13th orders. It is concluded that the developed model EMT simulations provide a realistic representation of the fundamental and harmonic behaviour of the actual network over a three-week time series.Overall, it is concluded that the established modelling environment provides a realistic representation of the actual network for the purpose of developing and testing harmonic mitigation algorithms to be overlaid on already included PV inverter models.The following report sets out the details of what is summarised above. In addition, an overview of the validation work is contained in a set of slides included here.